Gender dan GayaKepemimpinan Perempuan Di Jabatan Publik: Studi Fenomenologi Pelaksanaan Syariat Islam di Aceh - Rahma Hidayati; Nellis Mardhiah (Jurnal Community, 2018)
Acehnese women are known to be very unique, have distinctive moralist leadership styles and high fighting spirit with the nickname "Cut NyakDhien". These characteristics are inherent in their identity and able to integrate for the achievement of organizational goals. The objective of this study is the style of Acehnese women's leadership in public position. This study uses a qualitative method with a phenomenological approach that seeks to interpret events related to the situation holistically with empirical social reality. The results of this study are the presence of Acehnese women in the organization is very significant in the representation of organizational decision making. Representation also has a strategic function as communicative internalization that is firm in instilling the values of gender equality in every activity and the pattern of relations between the structure, role and function of a system. The moralist leadership pattern in organizational development in carrying out social and cultural duties and responsibilities can be done through a process of negotiation and mutual cooperation, where all forms of differences can find harmony with the distribution of roles and functions that are balanced from position and full commitment to Acehnese women in the Islamic law . Keywords: Gender, Leadership Style, Public Position, Islamic Shari'a